2001
DOI: 10.1046/j.1440-1843.2001.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle performance in endurance athletes and sedentary subjects

Abstract: Objective: The aim of this study was to determine whether whole‐body endurance training is associated with increased respiratory muscle strength and endurance. Methodology: Respiratory muscle strength (maximum inspiratory pressure (PImax)) and endurance (progressive threshold loading of the inspiratory muscles) were measured in six marathon runners and six sedentary subjects. Results: PImax was similar between the two groups of subjects but the maximum threshold pressure achieved was greater in marathon runner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
2
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 48 publications
1
20
2
4
Order By: Relevance
“…Eastwood et al (2001) investigated the effect of increased airway resistance in athletes and sedentary individuals and found that during exercise both groups maintained a low respiratory rate unlike our study in which individuals of both groups had a statistically significant increase in respiratory rate. Eastwood et al (2001) also observed a decrease in oxygen saturation at peak load, which was not observed in our study since our rate of arterial oxygenation remained unchanged. And as in our study, Eastwood et al (2001) demonstrated that the efficiency of the respiratory muscles was similar in both groups [32].…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…Eastwood et al (2001) investigated the effect of increased airway resistance in athletes and sedentary individuals and found that during exercise both groups maintained a low respiratory rate unlike our study in which individuals of both groups had a statistically significant increase in respiratory rate. Eastwood et al (2001) also observed a decrease in oxygen saturation at peak load, which was not observed in our study since our rate of arterial oxygenation remained unchanged. And as in our study, Eastwood et al (2001) demonstrated that the efficiency of the respiratory muscles was similar in both groups [32].…”
Section: Resultscontrasting
confidence: 63%
“…Contradicting the study by Ratnovsky et al (2005) which showed that it increases with high efforts and does nearly 10% of the inspiratory work [31]. Eastwood et al (2001) investigated the effect of increased airway resistance in athletes and sedentary individuals and found that during exercise both groups maintained a low respiratory rate unlike our study in which individuals of both groups had a statistically significant increase in respiratory rate. Eastwood et al (2001) also observed a decrease in oxygen saturation at peak load, which was not observed in our study since our rate of arterial oxygenation remained unchanged.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…One study has shown no difference in inspiratory muscle strength with increased respiratory muscle endurance in endurance trained athletes when compared to controls (Eastwood et al, 2001). In this study, changes in breathing pattern and active expiration through recruitment of additional respiratory muscles during exercise was suggested as the mechanism for greater respiratory muscle endurance (Eastwood et al, 2001). The majority of the current research using ET to alter respiratory muscle strength has been conducted using mainly rat models.…”
Section: Pulmonary Adaptationsmentioning
confidence: 59%
“…By increasing the expiratory flow rates, there could be a potential reduction on the pulmonary limitations discussed above. While this has been indirectly shown with endurance trained subjects, from hyperventilation and adoption of differing breathing patterns, the effects could potentially be even greater with HIT (Eastwood et al, 2001;Holm et al, 2004).…”
Section: Pulmonary Adaptationsmentioning
confidence: 99%